The potential health risks of heavy metals in cooked rice - Bakar, Nur Balkish Abu (Universiti Sains Malaysia, 2017)
Heavy metals in the environment become worldwide great concern due to their adverse effects to human health. This study was conducted to determine the concentration of cadmium (Cd), lead (Pb) and copper (Cu) in cooked rice from local production and imported from Thailand, Pakistan and India. Cooked rice were used because rice ingestion in one of the major pathway for heavy metals to accumulate in human body. The analysed heavy metals concentrations were utilized to measure Target Hazard Quotient (THQ) and Hazard Index (HI) to determine health risk assessment as indicator of risk associated with the consumption of heavy metal in contaminated rice. To evaluate the potential health risk of heavy metals, the method was used according to The United State Environmental Protection Agency (USEPA. In this study, three stages were involved; cooking process, acid digestion and lastly analysis of samples using Atomic Absorption Spectrometry (AAS). The mean concentration of heavy metals in cooked rice samples were 0.035 mg/kg for Cd, 0.428 mg/kg for Pb and 0.226 mg/kg for Cu. The heavy metal concentration in cooked rice samples were in the following order, Pb > Cu > Cd. There were no significant mean different for Cd and Cu concentrations from different countries while there were significant mean different for Pb concentration from different countries. Besides, the THQ values and the Hl value from different countries were less than one, indicating there were no adverse health effects to human. In conclusion, all cooked rice samples were safe for consumption as the THQ values and the HI values for all samples gives a value less than one implicating no carcinogenic health risk present in rice samples.